Safety Profile of Imatinib in Indian Chronic Myeloid Leukemia Patients (Health Renaissance, 2011)
Introduction: Imatinib mesylate has become the choice of drug in the treatment of chronic myeloid leukemia. Objective: To study safety profile of Imatinib (specific inhibitor or bcrabl tryosne kinase protein) in Philadelphia chromosome t {(9:22), bcr-abl} positive chronic myeloid leukemia (CML) chronic phase patients. Materials and Methods: After IEC clearance, 36, BCR-ABL positive CML patients in the chronic phase of the disease were recruited. Imatinib mesylate (Gleevec, Novartis), was started (400mg daily) and followed up weekly in first month, two weekly till three months & monthly thereafter. Safety profile data, recorded in pre-designed proforma, were analyzed for time of onset, duration and severity of adverse effects. Causality relationship of recorded adverse events was established with imatinib therapy using WHO-UMC criteria. Results: A total of 222 adverse events were reported in 36 CML-CP patients over 12 months of follow up. Thrombocytopenia was the most commonly reported in 60% of the patients followed by musculoskeletal (17%), dermatological (16%), gastrointestinal disturbances (13%), body weight changes (11%), superficial edema (8%) and liver enzyme rise (4%). More than 80% events reported within months of therapy which persisted for less than 3 months in most of the cases. No treatment was needed in 68% of cases while therapy alteration was not needed in 88% of cases. Most of the reactions (60%) had probable relationship with the therapy. Conclusion: Imatinib was well tolerated, having only mild to moderate grade of toxicities, mostly within 3 months of therapy and most of them persisted for less than 3 months of duration, requiring only symptomatic treatment and drug withhold or dose decrement in only few cases. Keywords: Safety profile; imatinib; causality assessment; adverse events. DOI: 10.3126/hren.v9i1.4358Health Renaissance, 2011: Vol.9 No.1:24-30